2015
DOI: 10.1038/srep16886
|View full text |Cite
|
Sign up to set email alerts
|

Expanding the scope of Metal-Free enantioselective allylic substitutions: Anthrones

Abstract: The highly enantioselective asymmetric allylic alkylation of Morita–Baylis–Hillman carbonates with anthrones is presented. The reaction is simply catalyzed by cinchona alkaloid derivatives affording the final alkylated products in good yields and excellent enantioselectivities.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 38 publications
0
5
0
Order By: Relevance
“…This challenge was expected to be a thorny problem not only due to the potential propensity of alkylation product 6 to C10 (anthrone numbering) racemization under the required basic conditions but also because of its perceived sensitivity to isomerize under the Lewis acid mediated spirocyclization conditions to form the next advanced intermediate, chiral pentacyclic compound 4 (viridicatumtoxin numbering). Although numerous asymmetric alkylations have been reported, a practical asymmetric alkylation of anthrones of type 7 was not available at the outset of this work.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…This challenge was expected to be a thorny problem not only due to the potential propensity of alkylation product 6 to C10 (anthrone numbering) racemization under the required basic conditions but also because of its perceived sensitivity to isomerize under the Lewis acid mediated spirocyclization conditions to form the next advanced intermediate, chiral pentacyclic compound 4 (viridicatumtoxin numbering). Although numerous asymmetric alkylations have been reported, a practical asymmetric alkylation of anthrones of type 7 was not available at the outset of this work.…”
Section: Resultsmentioning
confidence: 99%
“…Focusing on known asymmetric alkylation reactions, our initial studies pointed to phase transfer catalysts as promising for further studies. Brief exploration of phase transfer catalysts PTC1 (Corey et al) and PTC2 (Maruoka et al) and chiral base catalyst PTC3 (Hatakeyama et al) identified the Corey catalyst ( PTC1) as the most practical and efficient to pursue as a lead scaffold for further optimization (see Table , entries 1–3).…”
Section: Resultsmentioning
confidence: 99%
“…The MBH carbonates 2a–e were synthesized as described in the literature. , The MBH carbonates 2f–k were synthesized as follows: to a mixture of the corresponding aromatic aldehyde (5 mmol, 1 equiv) and the naphthyl acrylate (1.2 equiv) was added DABCO (1 equiv) and stirred for 45 min at room temperature. For liquid aldehydes, the reaction was performed in neat conditions, whereas 1 mL of MeCN was used as solvent for solid aldehydes, after which the mixture was diluted with CH 2 Cl 2 (2 mL) and directly purified by silica gel column chromatography to furnish the corresponding MBH alcohol.…”
Section: Experimental Sectionmentioning
confidence: 99%
“…The pioneering works of Trost, together with the seminal reports by Kim and Lu established the foundations of both the transition-metal-catalyzed and the Lewis-base-catalyzed AAA reactions (Scheme a). Although extensive efforts have been devoted to expanding their generality and harnessing their asymmetric potential, these transformations are mainly restricted to the use of stabilized or acidic C -nucleophiles, such as alkali-metal salts, active methylene compounds, or enolates (Scheme a). Conversely, the use of nonacidic or nonstabilized nucleophiles remains largely underdeveloped, being particularly elusive in the AAA catalyzed by chiral Lewis bases.…”
Section: Introductionmentioning
confidence: 99%
“…Another organocatalyst derived from Cinchona alkaloids, such as (DHQD) 2 AQN, was used by Rios et al to promote the allylic alkylation reaction of various MoritaÀBaylisÀHillman carbonates with anthrones that constituted important scaffolds in natural products and medicinal as well as agrochemical chemistry. 58 As shown in Scheme 26, this first use of anthrone 69 in reactions with Mor-itaÀBaylisÀHillman carbonates 66 (EWG ¼ CO 2 Me) performed in dichloromethane at 0 C in the presence of 20 mol% of (DHQD) 2 AQN led to the corresponding highly functionalised chiral anthrone derivatives 70 in moderate to excellent yields (55e96%) along with high enantioselectivities of up to 96% ee. When methyl esters (EWG ¼ CO 2 Me) exhibited an aromatic group (R), the enantioselectivities of the reactions were uniformly high (78e96%) while an aliphatic ester (R ¼ CH 2 Bn) led to an almost racemic product (4% ee) albeit in good yield (55%).…”
Section: Cinchona Alkaloid Catalystsmentioning
confidence: 99%